The emerging role of alternative splicing in senescence and aging. Issue 5 (13th July 2017) - Deschênes, Mathieu; Chabot, Benoit
Summary: Deregulation of precursor mRNA splicing is associated with many illnesses and has been linked to age‐related chronic diseases. Here we review recent progress documenting how defects in the machinery that performs intron removal and controls splice site selection contribute to cellular senescence and organismal aging. We discuss the functional association linking p53, IGF‐1, SIRT1, and ING‐1 splice variants with senescence and aging, and review a selection of splicing defects occurring in accelerated aging (progeria), vascular aging, and Alzheimer's disease. Overall, it is becoming increasingly clear that changes in the activity of splicing factors and in the production of key splice variants can impact cellular senescence and the aging phenotype.